2005
DOI: 10.1080/10611860500422958
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of clove oil and its potential in the treatment of vaginal candidiasis

Abstract: In the present study, we evaluated antimicrobial activity of clove oil against a range of fungal pathogens including that responsible for urogenital infection. Clove oil was found to possess strong antifungal activity against opportunistic fungal pathogens such as Candida albicans, Cryptococcus neoformans and Aspergillus fumigatus, etc. The oil was found to be extremely successful in the treatment of experimental murine vaginitis in model animals. On evaluating various formulations, topical administration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…HPLC analysis of clove oil and laboratory reagent (LR) grade eugenol (Oxford Chemicals, India) was done in isocratic mode by using Shimadu’s prominent HPLC system using a reverse phase C18 column [Phenomenex Luna, 5μ C18 (2) 100A (250×4.60 mm)], eluent: methanol/acetonitrile (70:30), UV detector: 254 nm, flow rate 0.5 ml/min, column temperature 40˚C. One hundred milligrams of EO was dissolved in 5 ml of mobile phase solvent and 20 µl was injected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC analysis of clove oil and laboratory reagent (LR) grade eugenol (Oxford Chemicals, India) was done in isocratic mode by using Shimadu’s prominent HPLC system using a reverse phase C18 column [Phenomenex Luna, 5μ C18 (2) 100A (250×4.60 mm)], eluent: methanol/acetonitrile (70:30), UV detector: 254 nm, flow rate 0.5 ml/min, column temperature 40˚C. One hundred milligrams of EO was dissolved in 5 ml of mobile phase solvent and 20 µl was injected.…”
Section: Methodsmentioning
confidence: 99%
“…Ahmad et al (2) evaluated antimicrobial activity of clove oil against a range of fungal pathogens including the ones for urogenital infection. Clove oil was found to possess strong antifungal activity against opportunistic fungal pathogens such as Candida albicans , Cryptococcus neoformans and Aspergillus fumigatus .…”
Section: Introductionmentioning
confidence: 99%
“…But essential oils have been used effectively against such infections since ancient times without side effects. Oils of Cymbopogon citratus and Syzygium aromaticum have been documented for their antifungal effects against oral and vaginal candidiasis under in vitro and in vivo studies and their specific anti-Candida activity against planktonic forms is well established (Knoblock et al, 1989;Abe et al, 2003;Ahmad et al, 2005;Khan and Ahmad, 2012). However, little is known about the spectrum of action of these oils against Candida biofilm cells.…”
Section: Introductionmentioning
confidence: 98%
“…Some research studies have reported antifungal activity of clove oil and eugenol against several yeasts and fungi (10)(11)(12)(13). Clove oil and eugenol have also been evaluated as antifungal agents in animal models (14).…”
Section: Introductionmentioning
confidence: 99%